Determinants of Left Ventricular Hypertrophy - Mercadier, J. J. (Immunology, Endocrine & Metabolic Agents in Medicinal Chemistry (Discontinued), 2006)
Left ventricular hypertrophy (LVH), defined as an increase in left ventricular mass, is one the aspect of the cardiac phenotype observed during hypertension and other conditions associated with a chronic increase in LV afterload. Since myocardial hypertrophy helps to normalize LV wall stress and the load of the constituting myocytes, LVH has long been considered to be a beneficial adaptive mechanism. However, LVH is also an independent risk factor for the occurrence of clinical events, including death. During the past 25 years, basic cardiac research has allowed to better understand the reasons for such a negative outcome. During the eighties, the other phenotypic characteristics of the hypertrophied LV have been established, showing a number of tissular, cellular and molecular alterations, the adaptive nature of which was clearly questionable. Since the beginning of the nineties, research has moved to the field of the mechanisms responsible for such changes and has allowed to identify a large number of triggers, initiators, signal transduction pathways and networks, effectors and counter-effectors responsible for LVH and the other phenotypic aspects of LV remodeling. Some of them referred to as
Keywords: mediators